Meditation retreats: Spiritual tourism well-being interventions. (October 2017) - Norman, Alex; Pokorny, Jennifer J.
Abstract: Meditation retreats now constitute a notable sub-section of the tourism industry, with examples found around the world. Despite this, meditation retreat tourism remains largely undocumented in scholarly literature. Findings from research of an overlapping phenomenon, spiritual tourism, suggest certain motivational themes may have great utility for helping to understand meditation retreat tourism practices. Notably absent from this research, however, is scientific investigation of the outcomes for tourists. Since the early 2000s, meditation has rapidly increased in popularity and social status, and is now promoted as a health and well-being practice. This paper uses literature on spiritual tourism, meditation practice outcomes, and well-being to argue that meditation retreat tourism functions as a self-administered well-being intervention. With this conceptual understanding, researchers can locate meditation retreat tourism within Western socio-historical discourse, and situate the phenomenon within the field of well-being studies so that these issues may be further investigated in their social and historical contexts. Highlights: Research shows time spent developing interpersonal skills and reflecting upon prudential value questions can be beneficial. Interest in meditation practices means meditation retreats are increasingly popular, but remain little understood by researchers. The spiritual tourism model enables meditation retreat participation to be seen as self-administered well-being intervention.